Music Restores Propriospinal Excitation During Stroke Locomotion - Peyre, Iseline; Hanna-Boutros, Berthe; Lackmy-Vallee, Alexandra; Kemlin, Claire; Bayen, Eléonore; Pradat-Diehl, Pascale; Marchand-Pauvert, Véronique (Frontiers in Systems Neuroscience, 2020)
Music-based therapy for rehabilitation induces neuromodulation at the brain level and improves the functional recovery. In line with this, musical rhythmicity improves post-stroke gait. Moreover, an external distractor also helps stroke patients to improve locomotion. We raised the question whether music with irregular tempo (arrhythmic music), and its possible influence on attention would induce neuromodulation and improve the post-stroke gait. We tested music-induced neuromodulation at the level of a propriospinal reflex, known to be particularly involved in the control of stabilized locomotion; after stroke, the reflex is enhanced on the hemiparetic side. The study was conducted in 12 post-stroke patients and 12 controls. Quadriceps EMG was conditioned by electrical stimulation of the common peroneal nerve, which produces a biphasic facilitation on EMG, reflecting the level of activity of the propriospinal reflex between ankle dorsiflexors and quadriceps (CPQ reflex). The CPQ reflex was tested during treadmill locomotion at the preferred speed of each individual, in 3 conditions randomly alternated: without music vs. 2 arrhythmic music tracks, including a pleasant melody and unpleasant aleatory electronic sounds (AES); biomechanical and physiological parameters were also investigated. The CPQ reflex was significantly larger in patients during walking without sound, compared to controls. During walking with music, irrespective of the theme, there was no more difference between groups. In controls, music had no influence on the size of CPQ reflex. In patients, CPQ reflex was significantly larger during walking without sound than when listening to the melody or AES. No significant differences have been revealed concerning the biomechanical and the physiological parameters in both groups. Arrhythmic music listening modulates the spinal excitability during post-stroke walking, restoring the CPQ reflex activity to normality. The plasticity was not accompanied by any clear improvement of gait parameters, but the patients reported to prefer walking with music than without. The role of music as external focus of attention is discussed. This study has shown that music can modulate propriospinal neural network particularly involved in the gait control during the first training session. It is speculated that repetition may help to consolidate plasticity and would contribute to gait recovery after stroke.